New Periodic Solutions for a Class of Zakharov Equations - Cong Sun; Shuguan Ji (Advances in Mathematical Physics)
Through applying the Jacobian elliptic function method, we obtain the periodic solution for a series of nonlinear Zakharov equations, which contain Klein-Gordon Zakharov equations, Zakharov equations, and Zakharov-Rubenchik equations.